Первый штурм - Г. А. Черкашин (История Отечества в романах, повестях, документах. Век XX, 1990)
Экземпляры: (20191023) / Инвентарный номер: 25869 / Цена: 2.60 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 26 / ББК: 84(2Рос=Рус)6